2019
DOI: 10.1088/2053-1583/aafc6e
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of graphene-based materials: real commercial products versus ideal graphene

Abstract: There are tens of industrial producers claiming to sell graphene and related materials (GRM), mostly as solid powders. Recently the quality of commercial GRM has been questioned, and procedures for GRM quality control were suggested using Raman Spectroscopy or Atomic Force Microscopy. Such techniques require dissolving the sample in solvents, possibly introducing artefacts.A more pragmatic approach is needed, based on fast measurements and not requiring any assumption on GRM solubility. To this aim, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 52 publications
8
65
0
1
Order By: Relevance
“…However, this method is expensive and liquid phase exfoliation is generally used for bulk manufacture . It is natural to ask how successful the manufacturers are at producing genuinely single layer graphene and to this end, there have been two major investigations of the quality of commercial graphene . Both concluded that the overall quality was poor and that most manufacturers were producing largely, or entirely, “nano‐graphite” rather than graphene, as defined by the ISO.…”
Section: Some Properties Of the Samples Studiedmentioning
confidence: 99%
“…However, this method is expensive and liquid phase exfoliation is generally used for bulk manufacture . It is natural to ask how successful the manufacturers are at producing genuinely single layer graphene and to this end, there have been two major investigations of the quality of commercial graphene . Both concluded that the overall quality was poor and that most manufacturers were producing largely, or entirely, “nano‐graphite” rather than graphene, as defined by the ISO.…”
Section: Some Properties Of the Samples Studiedmentioning
confidence: 99%
“…For producing graphene/ polymer composites even at low volume fractions, methods for scalable synthesis of graphene, such as shear liquid exfoliation [12][13] , that yield relatively large quantities of multi-layer graphene flakes need to be employed. In fact, in a recent paper 14 , it has been shown that the commercially available graphene with scalable production consists of few-layers of lateral size of only a few microns. Furthermore, in most cases the resulting graphene flakes are of small size (~3-5 μm) and of irregular shape.…”
Section: Introductionmentioning
confidence: 99%
“…ERG is made directly from the aqueous dispersion avoiding drying and powder handling steps that are required to make many current graphene products, compromising the quality of industrial products. 57 Other properties of the extended thin ERG films described in the present work also derive from cellulose properties. ERG is resistant to water but it may swell, depending on the cellulose content.…”
Section: The Multiple Roles Of Cellulose: Exfoliating Agent Adhesivementioning
confidence: 80%